Micelle modified-carbon nanosphere enhanced chemiluminescence from reactive oxygen species for the detection of hydrogen peroxide. Issue 13 (17th June 2015) - Pan, Feng; Wei, Pengkun; Zhang, Manlin; Lu, Chao
Abstract : Micelle modified-carbon nanospheres could enhance three chemiluminescent systems and can be used for the detection of hydrogen peroxide. Abstract : In this work, carbon nanospheres (CNSs) were prepared with glucose through a hydrothermal synthesis method. Subsequently, a cetyltrimethylammonium bromide (CTAB) bilayer was used to modify the surface of the as-prepared CNSs (denoted as CTAB–CNSs). Interestingly, it was found that CTAB–CNSs could significantly amplify chemiluminescence (CL) emissions from some reactive oxygen species systems, including the Co(ii )–H2 O2 –OH − system, ClO − system and ONOO − system. The CL intensity was proportional to the concentration of H2 O2 in the Co(ii )–H2 O2 –OH − system in a linear range of 5–1000 μM with a limit of detection of 2.6 μM ( S / N = 3). The enhancement mechanism of CTAB–CNS-amplified CL from the Co(ii )–H2 O2 –OH − system was investigated using the fluorescence spectra, CL spectrum, scavengers of reactive oxygen species, and UV-vis absorption spectra. The results indicated that the CTAB bilayer on the surface of CNSs could form a particular micelle microenvironment, facilitating the reaction between reactive intermediates and CNSs. Finally, this method has been successfully used to detect H2 O2 in river water and lake water samples, and the recoveries were from 96 to 110%. The relative standard deviation (RSD) for nine repeated measurements was less than 5%.